PERLINDUNGAN HUKUM TERHADAP DIREKSI PERSEROAN TERBATAS TERTUTUP YANG DIBERHENTIKAN SEMENTARA BERDASARKAN SURAT KEPUTUSAN DEWAN KOMISARIS TERKAIT DENGAN PERBUATAN MELAWAN HUKUM - Dara Adinda Tsuraya; Yurisa Martanti; M. Sudirman; Zainuddin (INTELIGENSIA MEDIA, 2025)
This study investigates the legitimacy and legal implications of the temporary dismissal of directors by the board of commissioners undertaken without adherence to the prescribed procedures, specifically the absence of an extraordinary general meeting of shareholders and the denial of the directors’ right to defend themselves. Pursuant to Law Number 40 of 2007 on Limited Liability Companies and Article 1365 of the Indonesian Civil Code, any dismissal conducted without lawful procedure entitles the directors concerned to institute legal proceedings before the court. A valid dismissal must be executed through an extraordinary general meeting of shareholders while safeguarding the directors’ right to present their defense, thereby ensuring the protection of their legal interests and determining whether the temporary dismissal should be upheld or annulled. The losses incurred as a consequence of such procedurally defective dismissals give rise to legal consequences in the form of claims based on procedural irregularities.